Investigating the antiinflammatuary effect of dexamethasone in an asthma mice model - Kirkil, Gamze; Muz, M. Hamdi; Deveci, Figen; Bulut, Hakan; Eroksuz, Yesari; Ilhan, Necip; Turgut, Teyfik (Turkish Assoc Tuberculosis & Thorax, 2005)
We performed an asthma mice model in this study and aimed to investigate the levels of mediators in bronchoalveolar lavage fluid (BALF), and lung tissue, and the pathological changes response to the steroid treatment. BALB/c mice divided into three groups. PBS was applied to group 1 (control group). Asthma model was performed by exposing to ovalbumin in group 2 and 3. DEX was injected to group 3. After the last DEX dose all of the mice were killed by cervical dislocation. The samples of BALF and lung tissue were obtained. IL-4 and IL-5 levels of all samples were measured and inflammatory cells were counted in BALF. Evident eosinophilia was determined in BALF of group 2. Eosinophil numbers were lower in group 3 when compared with group 2 and this was statistically significant (p<0.001). Inflammatory cell infiltration, eodema and hyperemia observed around the walls of bronchus and bronchiols in group 2. The lungs of group 3 had normal histological appearance. Both two cytokin levels of lung tissue were higher in group 2 than group 1, and this was statistically significant (for IL-4 p<0.003, and for IL-5 p<0.002). In group 3, both two cytokin levels were statistically lower than group 2 (for IL-4 p<0.001, and for IL-5 p<0.026). In BALF samples both two cytokin levels were higher in group 2 than group 1, and this was statistically significant (for IL-4 p<0.004, and for IL-5 p<0.001). In group 3, both two cytokin levels were lower than group 2, but it was not statistically significant (p> 0.05). In conclusion, it is thought that antiinflammatory effect of glucocorticoids occur by inhibiting the formation of IL-4, IL-5 and eosinophils.
Keywords: Asthma; mice model; interleukin-4; interleukin-5